(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2021)
Competition Competition Law has been introduced in Malaysia since the 1990s, but at that time, there was no specific law on competition. Provisions related to competition were embedded in various legislations, such as the Communications and Multimedia Act 1998 and Energy Commission Act 2001. The government finally took the initiative to introduce specific laws on competition, known as the Competition Act 2010, to show Malaysia’s integrity and commitment towards the spirit of market integration in the ASEAN region. Since then, Malaysia has witnessed the development of Competition Law, especially with regard to the implementation of such laws in various commercial sectors, including intellectual property. Nine years after the enactment of the Competition Act 2010, the Malaysia Competition Commission (MyCC) issued specific guidelines on intellectual property in response to the current commercial needs and to meet the aspirations set out in the Guidelines on Chapter 1 Prohibition (Anti-Competition Agreement). Therefore, this article aims to identify and discuss the development of Competition Law in Malaysia related to intellectual property. This article is a literature review that uses primary and secondary sources to obtain data. The result showed that even though MyCC has issued specific guidelines on intellectual property (Guidelines on Intellectual Property Rights and Competition Law) to resolve issues related to intellectual property, some improvements need to be made so that it can be implemented effectively. Keywords: Competition law, intellectual property, Guidelines for Intellectual Property Rights and Competition Law, MyCC, Malaysia